Co-expression analysis of lncRNA and mRNA identifies potential adipogenesis regulatory non-coding RNAs involved in the transgenerational effects of tributyltin - da Silva Lopes, Maria Fernanda [UNESP] (2023)
The obesity epidemic is considered a global public health crisis, with an increase in caloric intake, sedentary lifestyles and/or genetic predispositions as contributing factors. Although the positive energy balance is one of the most significant causes of obesity, recent research has linked early exposure to Endocrine-Disrupting Chemicals (EDCs) such as the obesogen tributyltin (TBT) to the disease epidemic. In addition to their actions on the hormonal profile, EDCs can induce long-term changes in gene expression, possibly due to changes in epigenetic patterns. Long non-coding RNAs (lncRNAs) are epigenetic mediators that play important regulatory roles in several biological processes, through regulation of gene transcription and/or translation. In this study, we explored the differential expression of lncRNAs in gonadal white adipose tissue samples from adult male C57BL/6J F4 generation, female C57BL/6J offspring exposed (F0 generation) to 50 nM TBT or 0.1% DMSO (control of vehicle) via drinking water provided during pregnancy and lactation, analyzing RNA-seq data from a publicly available dataset (GSE105051). A total of 74 lncRNAs were differentially expressed (DE), 22 were up-regulated and 52 were down-regulated in the group whose F4 ancestor was exposed in utero to 50nM TBT when compared to those exposed to 0.1% DMSO (control). Regulation of DE lncRNAs and their potential partner genes in gonadal white adipose tissue of mice ancestrally exposed to EDC TBT may be related to the control of adipogenesis, as pathway enrichment analyses showed that these gene partners are mainly involved in the metabolism of lipids and glucose and in insulin-related pathways, which are essential for obesity onset and control.